Management of Galassi type 3 Arachnoid cyst- A Case Report - Magar, Birat Thapa; Thapa, Dinesh K.; Tamrakat, Karuna; Nepal, Pankaj Raj (Eastern Green Neurosurgery, 2019)
Arachnoid cyst is a benign congenital lesion which can be located in various regions like; suprasellar, sylvian, posterior fossa, spine & so on. The most common location of arachnoid cyst is the middle fossa or sylvian fissure usually behind the greater wing of sphenoid bone (50%). Here we are presenting a case of a 59 year-old woman brought to the emergency department with history of sudden onset loss of consciousness associated with generalized tonic clonic seizure. CT-scanning of head showed Galassi type 3 arachnoid cyst. She was managed with fenestration and partial marsupialization of cyst with excellent outcome.